Minimizing the environmental impact of unused pharmaceuticals: Review focused on prevention - Paut Kusturica, Milica; Jevtic, Marija; Ristovski, Jovana Trifunovic (Frontiers in Environmental Science, 2022)
Pharmaceuticals are essential for human health, but they become an environmental concern when entering the environment which occurs when residues are excreted after consumption or when unused pharmaceuticals are discarded improperly. Although there are no developed detection methods for all pharmaceuticals that reach the ecosystem, certain groups have been proven to cause adverse effects on ecosystems, including increased mortality in aquatic species and changes in physiology, behavior, or reproduction. Particular attention is devoted to these groups of pharmaceuticals and their environmental impact. In this review, the authors suggest measures for the reduction of unused pharmaceuticals in the environment, with a strong emphasis on prevention. Various policy interventions are recommended across the lifecycle including source-directed, user-orientated, and waste management measures, to prevent the creation of household pharmaceutical waste and to ensure environmentally friendly ways of pharmaceutical household waste disposal. Preventive measures include rational pharmaceutical consumption, prescribing greener drugs, or designing pharmaceuticals that are benign and easily biodegradable, improved disease prevention, personalized medicine, enhanced dimensioning of pack sizes, and marketplaces for redistribution of unused pharmaceuticals. The next step is to prevent unavoidable waste to reach the environment, so proper collection and disposal of unused pharmaceuticals is of utmost importance. Finally, educating health professionals and the public and partnership between environmental and healthcare scientists are of vital significance in all stages of the pharmaceuticals’ lifecycle. Minimalization of the level of pharmaceuticals in the environment will benefit human life.